TRANSFER DANA DALAM PERSPEKTIF HUKUM ISLAM - Khalil, Abdul Wahab (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2014)
This research aims to describe the concept of money transfer in fiqh, and investigate its relevance to banking issues at this time. The study begins by explaining the meaning of money transfer, its classification, and its process. The approach used in this research is descriptive-qualitative approach, because this study is intended to reveal and describe the money transfer seen from a fiqh perspective. By using research methods outlined above, it can be concluded that that there are two kinds of transfer; domestic transfer and cross-country transfer. Domestic transfer is categorized as â€œWakalah bi ajrâ€, thus it is allowed in Islamic fiqh with the terms that the service provided by the bank is in respect of the transfer of rational activity and does not exceed the line of reasonableness. Meanwhile, the cross-border transfer, the contemporary scholars have different opinions. Many of them forbid it, and some of them legalize. Here, the author chooses the opinion stating the validity of cross-country transfer transaction, because it is very urgent in the life of the global communities.